1, 25-Dihydroxy vitamin D3 stimulates system A amino acid transport in primary human trophoblast cells. (15th February 2017) - Chen, Yi-Yung; Powell, Theresa L.; Jansson, Thomas
Abstract: Vitamin D deficiency during pregnancy is linked to adverse perinatal outcomes such as small for gestational age infants. Recent evidence suggests that changes in placental amino acid transport contribute to altered fetal growth. We tested the hypothesis that 1, 25-dihydroxy vitamin D3 increases the gene expression of System A and L amino acid transporter isoforms and stimulates placental amino acid transport activity in cultured primary human trophoblast cells mediated by mTOR signaling. Treatment with 1, 25-dihydroxy vitamin D3 significantly increased mRNA expression of the System A isoform SNAT2 and System A activity, but had no effect on System L and did not affect mTOR signaling. siRNA silencing of the vitamin D receptor prevented 1, 25-dihydroxy vitamin D3 -stimulated System A transport. In conclusion, 1, 25-dihydroxy vitamin D3 regulates System A activity through increased mRNA expression of SNAT2 transporters. Effects on placental amino acid transport may be the mechanism underlying the association between maternal vitamin D status and fetal growth. Highlights: Effects of vitamin D on primary human trophoblast amino acid transport were studied. 1, 25-dihydroxy vitamin D3 increased mRNA expression of the System A isoform SNAT2. 1, 25-dihydroxy vitamin D3 stimulated system A amino acid transport activity. Trophoblast mTOR signaling was not regulated by1, 25-dihydroxy vitamin D3 . Altered placental amino acid transport may link maternal vitamin D to fetal growth.